PERAN ORANG TUA DALAM PENDIDIKAN AGAMA TERHADAP PEMBENTUKAN KEPRIBADIAN ANAK - Mardiyah Mardiyah (Jurnal Kependidikan, 2017)
The role of parents as the first educators and primary injecting mental development of children. Religious education should be able to color the child's personality, so religion was actually to be part of his personality will be in control of his life in the future. In order to achieve the formation of a good personality, then the religious education should be given to parents who truly reflected religion in attitudes, behavior, gestures, how to dress, how to speak, how to deal with the issueand the overall personality. In short it can be said that religious education will be successful, if the teachings of that religion reflected in the personal life and parents themselves.